Variación genética entre procedencias de Pinus hartwegii a los 5 años de edad - Loya Rebollar, Esperanza (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
In order to determine possible altitudinal pattern of genetic variation among populations of Pinus hartwegii in plants growing in a provenance test established in 1850 m. They were open-pollinated seeds collected from 13 natural populations along an altitudinal gradient (3150 to 3700 m above sea level, a population every 50 m difference in altitude), in the Peak National Park Tancítaro, Michoacán, Mexico. Plants were grown in a nursery and then settled on a design of a randomized complete block in a common garden test which evaluated when they were five years old. The variables studied were height, elongation of the bud, basal diameter, dry weight, resistance to cavitation, chlorophyll a and b. Significant differences among provenances in: total elongation (P=0.0008), growth rate (P =0.0014), final height (P =0.015) and basal diameter (P=<.0001). Similarly the analysis of variance showed significant differences for the variables: dry weight of needles (P=<.0001), dry weight of branches (P=0.0045), stem dry weight (P=0.0027) and total dry weight (P=0.0003). In addition we found a significant association between growth parameters and altitude of origin of populations in total elongation (r 2 =0.0004, P=0.6958), growth rate (r 2 =0.6899, P=0.0004), final height (r 2 =0.8336, P=<.0001) and basal diameter (r 2 =0.6715, P=0.0003). We also found significant association between dry weight and altitude of origin of populations in dry weight of needles (r 2 =0.7138, P=0.0003), dry weight of branches (r 2 =0.7356, P=0.0002), stem dry weight (r 2 =0.7599, P=<.0001) and total dry weight (r 2 =0.7522, P=0.0001).

Con el propósito de determinar un posible patrón de variación genética altitudinal entre poblaciones de Pinus hartwegii, en plantas que crecen en un ensayo de procedencias establecido en 1850 m de altitud. Fueron colectadas semillas de polinización abierta de 13 poblaciones naturales a lo largo de un gradiente altitudinal (3150 a 3700 m de altitud, una población cada 50 m de diferencia de altitud), en el Parque Nacional Pico de Tancítaro, Michoacán, México. Las plantas fueron cultivadas en un vivero y luego se estableció en un diseño de bloques completos al azar en una prueba de jardín común y donde se evaluaron cuando tenían cinco años de edad. Las variables evaluadas fueron altura, elongación de la yema apical, diámetro basal, peso seco, resistencia a la cavitación, contenido de clorofila a y b. Se encontraron diferencias significativas entre procedencias en: elongación total (P=0.0008), tasa de crecimiento (P=0.0014), altura final (P=0.015) y diámetro basal (P=<.0001). De la misma manera el análisis de varianza mostró diferencias significativas para las variables: peso seco de acículas (P=<.0001), peso seco de ramas (P=0.0045), peso seco del tallo (P=0.0027) y peso seco total (P=0.0003). Además de se encontró una asociación significativa entre los parámetros de crecimiento y la altitud de origen de las poblaciones en elongación total (r 2 =0.0004, P=0.6958), tasa de crecimiento (r 2 =0.6899, P=0.0004), altura final (r 2 =0.8336, P=<.0001) y diámetro basal (r 2 =0.6715, P=0.0003). También se encontró asociación significativa entre el peso seco y la altitud de origen de las poblaciones en peso seco de acículas (r 2 =0.7138, P=0.0003), peso seco de ramas (r 2 =0.7356, P= 0.0002), peso seco de tallo (r 2 =0.7599, P=<.0001) y pesos seco total (r 2 =0.7522, P=0.0001).
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; IIAF-M-2012-0009; Clorofila total; Cavitación; Conductividad hidráulica específica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1859